THEORETICAL BASIS OF THE USE OF DIGITAL TECHNOLOGIES IN THE PROCESS OF CREATING A DIGITAL PRODUCT PASSPORT OF PRODUCTS (Marketing Journal, 2025)
The article examines the concept of the digital product passport within the framework of the EU Ecodesign for Sustainable Products Regulation (ESPR), as well as modern digital technologies that support its implementation. The digital product passportʼs core function is highlighted as ensuring transparent provision of life-cycle data to consumers, regulators and business entities through digital identification tools. The study analyzes how blockchainʼs immutable ledger, smart contracts and tokenization enable products to be integrated into the digital ecosystem as real assets and ensure reliable management of ownership rights and transactions. The article also explores hybrid architectures combining on-chain and off-chain approaches, as well as multi -chain networks, and their role in meeting scalability, privacy and interoperability requirements. The integration of the DPP, blockchain and tokenization is evaluated as a new digital governance model for global supply chains and is interpreted as strategic infrastructure that enhances sustainability, transparency and competitiveness.
Keywords: digital product passport (DPP); digital identification; blockchain technology; tokenization; QR code; NFC; RFID technologies; sustainable and circular economy; ESPR regulation